2011
DOI: 10.3109/14992027.2010.542492
|View full text |Cite
|
Sign up to set email alerts
|

Cortical maturation and behavioral outcomes in children with auditory neuropathy spectrum disorder

Abstract: Objective Auditory Neuropathy Spectrum Disorder (ANSD) affects nearly 10% of patients with sensorineural hearing loss. While many studies report abnormalities at the level of the cochlea, auditory nerve and brainstem in children with ANSD, much less is known about their cortical development. We examined central auditory maturation in 21 children with ANSD. Design Morphology, latency and amplitude of the P1 Cortical Auditory Evoked Potential (CAEP) were used to assess auditory cortical maturation. Children’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
96
7
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 46 publications
18
96
7
6
Order By: Relevance
“…At this moment, the P1 component is characterized as a prominent positive peak that is gradually defined with the maturational process (4,13) . This finding was previously described in children with Auditory Neuropathy Spectrum Disorder, who used Hearing Aids (HA) (23) . A quick rate of P1 development following the activation of cochlear implants in children operated during the sensitive period, that is, up to three years and six months of age, has been described in literature.…”
Section: Discussionsupporting
confidence: 78%
“…At this moment, the P1 component is characterized as a prominent positive peak that is gradually defined with the maturational process (4,13) . This finding was previously described in children with Auditory Neuropathy Spectrum Disorder, who used Hearing Aids (HA) (23) . A quick rate of P1 development following the activation of cochlear implants in children operated during the sensitive period, that is, up to three years and six months of age, has been described in literature.…”
Section: Discussionsupporting
confidence: 78%
“…This explains the presence of LLRs in the absence of ABRs in individuals with auditory dys-synchrony. However, LLRs were present in a larger percentage of the participants of the present study compared to the figures reported by Rance et al [10] and Sharma et al [27] . Rance et al [10] found that N1-P2 was absent in 50% of the participants of their study; they attributed this absence to impaired speech perception.…”
Section: Discussioncontrasting
confidence: 75%
“…Rance et al [10] found that N1-P2 was absent in 50% of the participants of their study; they attributed this absence to impaired speech perception. In a retrospective analysis of the results from 21 children with ANSD, Sharma et al [27] reported that 38% of the children showed LLRs that were normal in all respects; 33% showed LLRs with normal morphology but with prolonged latency and decreased amplitude; and in the remaining 29%, the morphology of the LLRs was so poor that the latency and amplitude could not be measured.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, em uma conferência realizada na cidade de Como na Itália, em junho de 2008, cientistas e clínicos com experiência em dessincronia auditiva, reuniram-se e definiram que a melhor nomenclatura a ser utilizada seria DENA, pois o termo neuropatia auditiva havia ganhado ampla aceitação, tanto entre os profissionais, quanto entre os pais, e o termo espectro expande o conceito desta desordem permitindo incluir outros locais de lesão, além do nervo coclear (HAYES, 2008;SHARMA et al, 2011).…”
Section: Revisão De Literaturaunclassified
“…Na DENA a população de neurônios do VIII nervo e tronco encefálico é ativada de forma anormal ou dessincrônicos, levando a uma alteração no desenvolvimento cortical e, consequentemente, a uma diminuição na capacidade de aquisição de fala e linguagem nestas crianças (SHARMA et al, 2011).…”
Section: Revisão De Literaturaunclassified